The forms of the call in the supplication of Kumayl: a grammatical and semantic study (Journal of Misan Researches, 2024)
The vocative style is an integrated linguistic phenomenon at the levels of the language (sound, morphology, semantics, and pragmatics). This phenomenon cannot be studied and known at any level, regardless of the other levels. The separation between them here is for the purposes of research and study, so the researcher decided to study this method. Within two levels of language, the grammatical level and the semantic level associated with it, it adopted a descriptive analytical approach to describe the grammaticality of this method and explain its significance, adopting the vision of scholars in describing the methods of appeal mentioned in this supplication, and analyzing it in a grammatical and semantic analysis according to what is required by the context in which it appears. in it, Therefore, the research was based on two things: studying the grammatical style of the call to prayer in Kumayl’s supplication, and deducing the semantic meanings that can be read and inferred from the forms of the call in each stanza of this supplication, this requires the student to link the style of the call to the circumstances and situations in which it was used, to reveal the semantic meanings generated in it.